Framing False Political Narratives: Computational Propaganda, Fake News And Manipulation And Pakistan Social Media In 2025 - Awan, Muhammad Waqas; Ansari, Noman Ahmed; Ismail, Asif (Regional Lens, 2025)
The study investigated perpetuation of false narratives and political manipulation through fake news, misinformation, disinformation and computational propaganda in digital ecosystem of Pakistan in 2025. The study critically reviewed role of automation, online algorithms and coordinated human networks curtailing cyber security in political spheres. The viral political news stories of social media have been selected for content analysis employing purposive sampling technique. Exerting theoretical foundations from Framing theory and Propaganda model the study analyzed the key propaganda techniques, frames, patterns and major themes employed for shaping political discourses of Pakistani public. The findings suggested that fake AI driven technologies such as online algorithms, computational propaganda techniques, automation and intensify political polarization and serve as tool for production, consumption and dissemination of fake news and false narratives targeted to frame false narratives through manipulative propaganda techniques of political issues and news stories. The study highlighted urgent need to develop AI powered cyber security frameworks for detection of fake news and control information bias in order to enhance credibility and trustworthiness in digital spaces.